2023
DOI: 10.1080/14756366.2023.2281260
|View full text |Cite
|
Sign up to set email alerts
|

New spiro-indeno[1,2- b ]quinoxalines clubbed with benzimidazole scaffold as CDK2 inhibitors for halting non-small cell lung cancer; stereoselective synthesis, molecular dynamics and structural insights

Assem Barakat,
Saeed Alshahrani,
Abdullah Mohammed Al-Majid
et al.

Abstract: Despite the crucial role of CDK2 in tumorigenesis, few inhibitors reached clinical trials for managing lung cancer, the leading cause of cancer death. Herein, we report combinatorial stereoselective synthesis of rationally designed spiroindeno[1,2- b ]quinoxaline-based CDK2 inhibitors for NSCLC therapy. The design relied on merging pharmacophoric motifs and biomimetic scaffold hopping into this privileged skeleton via cost‐effective one-pot multicomponent [3 + 2] c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Targeting CDK2 offers a strategic approach to impede cancer cell division, and ongoing research aims to optimize CDK2 inhibitors for enhanced efficacy and reduced side effects, highlighting its potential as an innovative avenue in cancer therapy. We built upon the groundwork established by benchmark oxindole-based CDK2 inhibitors ( I ) ( Luk, 2004 ; Venkanna, et al, 2020 ; Bramson, et al, 2001 ) and spiro ( Al-Jassas, et al, 2023 ; Barakat, et al, 2023 ) anti-cancer agents recognized for their kinase inhibition, specifically those aimed at CDK2. This rational study involved a detailed exploration of the CDK2 inhibitory potential within the investigated series, as depicted in Figure 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeting CDK2 offers a strategic approach to impede cancer cell division, and ongoing research aims to optimize CDK2 inhibitors for enhanced efficacy and reduced side effects, highlighting its potential as an innovative avenue in cancer therapy. We built upon the groundwork established by benchmark oxindole-based CDK2 inhibitors ( I ) ( Luk, 2004 ; Venkanna, et al, 2020 ; Bramson, et al, 2001 ) and spiro ( Al-Jassas, et al, 2023 ; Barakat, et al, 2023 ) anti-cancer agents recognized for their kinase inhibition, specifically those aimed at CDK2. This rational study involved a detailed exploration of the CDK2 inhibitory potential within the investigated series, as depicted in Figure 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Barakat research group has reported a combinatorial stereoselective synthesis of rationally designed spiroindeno [1,2- b ]quinoxaline-based CDK2 inhibitors III for non-small cell lung cancer (NSCLC) therapy ( Barakat, et al, 2023 ). Among the derivatives tested, hit III emerged as the most promising, exhibiting potent inhibitory effects against A549 cells and normal lung fibroblasts Wi-38, with an IC 50 value of 54 nM and a selectivity index (SI) of 6.64.…”
Section: Introductionmentioning
confidence: 99%